Budget Ratcheting in Indonesia and The Implementation of Performance-Based Budgeting System During Pandemic: Budget Ratcheting in Indonesia and The Implementation of Performance-Based Budgeting System During Pandemic - Ade Marsinta Arsani; Pardomuan Robinson Sihombing (Jurnal Mantik, 2020)
In Indonesia, the regulation emphasizes the implementation of a performance-based budgeting system. However, the implementation of this system is questioned as the ratcheting effect tends to occur in the budgeting process in local government. The inefficiency that arises due to the occasion should be reduced by transforming it into the performance-based system, especially when a pandemic occurs. Reallocation of budget produced by incremental-line system should be implemented to minimize the risk of the pandemic on social welfare. The data used in this model are APBD data in 2013-2108 from the Ministry of Finance. Regression models and study literature are used in this study to identify the budget ratcheting that occurred in Indonesia and examine the implementation of performance-based budgeting that can reduce the occurrence of government budget behavior bias in the form of a ratchet effect when a pandemic occurs. The result of this study shows that there is an indication of the existence of asymmetric ratchet. As it may lead to inefficiency, to face a pandemic situation, the government should conduct performance target adjusting and program restructuring by reallocating the budget.